A Cooperative Dynamic Approach to Pairs Trading. (13th October 2021) - Ramos-Requena, J. P.; López-García, M. N.; Sánchez-Granero, M. A.; Trinidad-Segovia, J. E.
Abstract : Based on recent works on stocks comovement, Pairs Trading's strategy is enhanced by reducing the stock universe to the stocks with the lower volatility on a given date. From this universe of low volatility stocks, pairs are selected by looking for pairs whose series present a high degree of antipersistence. Finally, a "reversion to the mean" strategy is applied to these pairs. It is shown that, with this approach to Pairs Trading, positive results can be obtained for stock from the Nasdaq stock exchange, mainly during bull markets and low volatility periods.